Application of Levine’s Model in Nursing Care of Patient with Diabetic Foot: A Case Study - Laksmi, Ida Ayu Agung; Kristianto, Heri; Suharsono, Tony (Journal of A Sustainable Global South; Vol 4 No 1 (2020): February 2020DO - 10.24843/jsgs.2020.v04.i01.p02, 2020)
Diabetic foot is such a life threatening condition for people with Diabetes Mellitus which it can be result in hemodynamic instability and loss of consciousness. In order to improve quality of nursing care in patient with diabetic foot, nurses should apply a nursing model approach. Levine conservation theoretical model is one of comprehensive model theory that can be applied in patients with critical diabetic foot in Emergency Department (ED). This case study describes a nursing care using Levine's Conservation Model to care for a patient with diabetic foot.  This study was a case study with a single case design. Data were collected using physical assessment, written communications with the patient, interviews patient family members, and observing the patient during intensive care in the ED of Lawang General Hospital on December 21th, 2015. Levine's Conservation Model used as the nursing guideline successfully identified patient issues including ineffective breathing pattern as a major priority of energy conservation problem and damage tissue integrity as a problem of structural conservation. Both of conservation problem were caused by patient's personal integrity conservation maladaptive that caused by ineffective therapeutic regimen management. Levine’s conservation model is useful to investigate nursing problem and applicable to solve the emergency condition of damage tissue integrity in patients with diabetic foot. Index Terms — diabetic foot, nursing care, levine’s conservation model.